2021
DOI: 10.31557/apjcc.2021.6.2.141-147
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practices of Breast Self-Examination Amongst Indian Women: A Pan-India Study

Abstract: Objective: Breast Cancer is the leading cause of mortality and morbidity amongst Indian females. Breast self-examination (BSE) as an early detection modularity can have a profound effect on lowering mortality, if it is practiced regularly. The aim of this study was to assess the knowledge, attitude, and practice of Breast Self-examination amongst Indian women, aged 30 years and above. Methods: A validated questionnaire, consisting 35 questions measuring ‘Knowledge, Attitudes and Practice of Breast Self-Examina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 0 publications
0
10
0
3
Order By: Relevance
“…A Turkish study concluded that nurses as health care professionals could play a key role in educating women about BSE. 9 Study shows that these personal fears such as the fear of physicians and doctors, fear of the results as well as the fear of hospitals are some of the main barriers for not practicing screening of breast cancer 14 .…”
Section: Education Status Discussionmentioning
confidence: 99%
“…A Turkish study concluded that nurses as health care professionals could play a key role in educating women about BSE. 9 Study shows that these personal fears such as the fear of physicians and doctors, fear of the results as well as the fear of hospitals are some of the main barriers for not practicing screening of breast cancer 14 .…”
Section: Education Status Discussionmentioning
confidence: 99%
“…A study involving 356 female Information Technology (IT) professionals in India's Silicon Valley [5], identified that BSE knowledge (mean score 18.17 ± 2.90) and practice (mean score 19.11 ± 5.08) were extremely correlated. Other studies [13,14] involving Indian women have also reported poor BSE knowledge and/or practice. In another study [12] involving 320 Sikkimese nursing staff, the majority (79.1 %) were aware of CCS, meanwhile, only 11.9 % had ever undergone CCS.…”
Section: Figure 1 Common Factors That Increase (Left) and Reduces (Right) The Risk Of Breast Cancermentioning
confidence: 95%
“…____________________________________________________________________ INDEX DE ENFERMERÍA/TERCER TRIMESTRE 2023, VOL. 32, N. 3 2…”
Section: Originalesmentioning
confidence: 99%